ZUR VERWANDTSCHAFTSTERMINOLOGIE DER MATSIGENKA, OST-PERU - Löffler, Lorenz G.; Baer, Gerhard (L’Uomo società tradizione sviluppo, 2019)
The authors disagree with Casevitz's findings (1976). Casevitz found that Matsigenka nomenclature and recognized lines of descent were both founded on four genealogical levels (grandparents, parents, Ego, and children) but saw no direct relation between them. He stressed the structural necessity arising from the existence of four local groups as an element fostering preferential marriage with the female patrilateral cross-cousin in her place of residence. Setting aside the question of any matrimonial “preference”, the present authors show that the husband”s choice is oriented towards female cross-cousins because of the local exogamous norm. Given the matrilocal residence pattern, Ego”s four grandparents come from the four different localities where the four couples of great-grandparents lived. Therefore Ego finds “sisters” in the local groups of FF and MM and has no choice but to marry women (“cousins”) from the local groups of FM and MF. In the absence of descent groups, there is nevertheless no doubt that marriages are considered in terms of “alliance” between local groups. What is extremely interesting is the occasional convergence, at the terminological level, of grandparents” relatives and individuals of the generation of the grandchildren (G-2) with collateral members of the same generation, e.g., HFF(B). This convergence appears in similar fashion in the four class systems, but in the Matsigenka system this is not carried over into the series of convergences present in the other systems.